Murabahan in Islamic Jurisprudence and Indonesian Islamic Banks A Case Study of BPRS in Yogyakarta - Mohammad Salim Salim (Program Pascasarjana Universitas Islam Negeri Sunan Kalijaga, 2022)
et,1/adil,c.1